101 uses for an Eveready - National Carbon Company, Inc. (American Ever Ready Works, 1917)
An advertising pamphlet for Eveready flashlights, includes an explanation of how an electric flashlight will aid the user along with how it operates with the use of an Eveready Tungsten Battery. Features illustrations of various models along with a list of available products under the following lines: Tubular Tungsten Flashlights, Nickel Plated Tubular Tungsten Flashlights, Nickel Plated Vest Pocket Tungsten Flashlights, Tungsten House Lamps, Electric Tungsten Candles, and Electric Tungsten Lanterns. Also includes a list entitled "101 Uses for a Flashlight."
Keywords: Electric lamps; Flashlights; Electric batteries; Tungsten lamps; Eveready Battery Company; Advertising